Securing the airway in a child with tracheal agenesis – an alternative perspective - Slavomir Nosal; Mirko Zibolen; Katarina Matasova; Milan Dragula; Martin Ciljak; Dalibor Murgas; Julian Hamzik (Videosurgery and Other Miniinvasive Techniques)
Tracheal agenesis is an extremely rare, typically fatal congenital anomaly characterised by typical clinical manifestation, failed endotracheal intubation and difficult emergency management. The prognosis and possibility of surgical correction rest on early diagnosis, anatomy, birth weight, and associated anomalies. Tracheal agenesis causes considerable resuscitation difficulties immediately after birth, as tracheal intubation is impossible. Although emergency management, by either bag and mask ventilation or oesophageal intubation, provides some pulmonary gas exchange through tracheo-oesophageal connection, they are associated with overdistension of the stomach and the risk of stomach perforation. We have performed selective intubation of the distal trachea in a child with tracheal agenesis through the tracheo-oesophageal connection with the help of a fibroendoscope. A standard guide wire was passed through the working port of the flexible endoscope and under direct vision was directed through the tracheo-oesophageal connection into the distal trachea. At this point, the endoscope was removed, leaving the guide wire in place. The endotracheal tube size 2 Fr was passed over the guide wire into the distal trachea. The infant showed dramatic improvement and maintained good saturations on mechanical ventilation. The infant was taken for a computed tomography (CT) scan, which showed Floyd’s type II tracheal agenesis, the oesophagus connecting with the distal trachea before it bifurcates. The endotracheal tube was seen ending in the carina. Transoesophageal intubation of the short distal segment of the trachea through the tracheo-oesophageal connection might offer a new perspective for short-term securing of the airway in a child with tracheal agenesis and should be considered in any child with suspected tracheal agenesis to buy the time while evaluating the exact anatomy of the anomaly and the possibility of tracheal reconstruction in selected cases.